Niche, not phylogeny, governs the response to oxygen availability among diverse Pseudomonas aeruginosa strains - Shewaramani, Sonal; Kassen, Rees (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa, a ubiquitous opportunistic pathogen, is a leading cause of chronic infection of airways in cystic fibrosis (CF) patients. Chronic infections typically arise from colonization by environmental strains, followed by adaptation of P. aeruginosa to the conditions within the CF airway. It has been suggested that oxygen availability can be an important source of selection causing trait changes associated with the transition to chronic infection, but little data exists on the response of P. aeruginosa to varying levels of oxygen. Here, we use a diverse collection of P. aeruginosa strains recovered from both CF patients and environmental sources to evaluate the role of oxygen availability in driving adaptation to the CF lung while also accounting for phylogenetic relatedness. While we can detect a signal of phylogeny in trait responses to oxygen availability, niche of origin is a far stronger predictor. Specifically, strains isolated from the lungs of CF patients are more sensitive to external oxidative stress but more resistant to antibiotics under anoxic conditions. Additionally, many, though not all, patho-adaptive traits we assayed are insensitive to oxygen availability. Our results suggest that inferences about trait expression, especially those associated with the transition to chronic infection, depend on both the available oxygen and niche of origin of the strains being studied.